Efficient N-arylation of amines catalyzed by Cu-Fe-hydrotalcite - Jadhav, Vinod H.; Dumbre, Deepa K.; Phapale, Vilas B.; Borate, Hanumant B.; Wakharkar, Radhika D. (Catalysis Communications, 2007)
An efficient N-arylation of amines with aryl halides in presence of heterogeneous recyclable Cu-Fe-hydrotalcite catalyst has been developed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: amines; Aryl halides; Cu-Fe-hydrotalcite; heterogeneous catalyst; N-arylation

Thermally decomposed Cu-Fe-hydrotalcite. a novel highly active catalyst for o-arylation of naphthol and phenols by aryl halides - Choudhary, Vasant R.; Dumbre, Deepa K.; Yadav, P. N.; Bhargava, Suresh Kumar (Catalysis Communications, 2012)
A novel, efficient and environmentally benign method has been reported for the synthesis of diaryl ethers by the o-arylation of napthol or phenols with aryl halides in dimethylformamide (as a solvent) under reflux, using a novel heterogeneous catalyst (having redox properties), obtained from thermal decomposition of Cu-Fe at 600 degrees C in the absence of externally added base. The catalyst comprises Cu(II) and Fe(III) species (oxides and hydroxides), which are uniformly distributed during the catalyst formation. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Aryl halides; C-O cross coupling reaction; Cu-Fe-hydrotalcite; Naphthol; o-Arylation; Phenols

Mesoporous, ligand free Cu-Fe solid catalyst mediated CS cross coupling of thiols with aryl halides - Dumbre, Deepa K.; Selvakannan, P. R.; Patil, S. K.; Choudhary, Vasant R.; Bhargava, Suresh Kumar (Applied Catalysis A-General, 2014)
Solid catalyst derived from Cu-Fe hydrotalcite was demonstrated to be a novel, ligandless, efficient and environmentally greener catalyst for the synthesis of diaryl sulfurs from the C-S cross coupling reaction of substituted thiols with different aryl halides. This catalyst has shown higher product yield in the presence of dimethylformamide (as a solvent) and K2CO3 (as a base) at 120 C. Influence of different solvents and bases on the product yield has also been investigated. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity. The catalyst has been fully characterized for its surface and bulk properties and the mesoporous CuO:Fe2O3 phase was attributed for its catalytic activity towards S-arylation reactions. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: C-S cross coupling; Cu-Fe-hydrotalcite; S-arylation